A guaranteed income intervention to improve the health and financial well-being of low-income black emerging adults: study protocol for the Black Economic Equity Movement randomized controlled crossover trial - Sheri A. Lippman; Margaret K. Libby; Michelle K. Nakphong; Abigail Arons; Monica Balanoff; Adrienne Rain Mocello; Emily A. Arnold; Starley B. Shade; Fahad Qurashi; Alexandria Downing; Alexis Moore; William H. Dow; et al. (Frontiers Media S.A., 2023)
BackgroundEconomic inequity systematically affects Black emerging adults (BEA), aged 18-24, and their healthy trajectory into adulthood. Guaranteed income (GI)-temporary, unconditional cash payments-is gaining traction as a policy solution to address the inequitable distribution of resources sewn by decades of structural racism and disinvestment. GI provides recipients with security, time, and support to enable their transition into adulthood and shows promise for improving mental and physical health outcomes. To date, few GI pilots have targeted emerging adults. The BEEM trial seeks to determine whether providing GI to BEA improves financial wellbeing, mental and physical health as a means to address health disparities.Methods/designUsing a randomized controlled crossover trial design, 300 low-income BEA from San Francisco and Oakland, California, are randomized to receive a $500/month GI either during the first 12-months of follow-up (Phase I) or during the second 12-months of a total of 24-months follow-up (Phase II). All participants are offered enrollment in optional peer discussion groups and financial mentoring to bolster financial capability. Primary intention-to-treat analyzes will evaluate the impact of GI at 12 months among Phase I GI recipients compared to waitlist arm participants using Generalized Estimating Equations (GEE). Primary outcomes include: (a) financial well-being (investing in education/training); (b) mental health status (depressive symptoms); and (c) unmet need for mental health and sexual and reproductive health services. Secondary analyzes will examine effects of optional financial capability components using GEE with causal inference methods to adjust for differences across sub-strata. We will also explore the degree to which GI impacts dissipate after payments end. Study outcomes will be collected via surveys every 3 months throughout the study. A nested longitudinal qualitative cohort of 36 participants will further clarify how GI impacts these outcomes. We also discuss how anti-racism praxis guided the intervention design, evaluation design, and implementation.DiscussionFindings will provide the first experimental evidence of whether targeted GI paired with complementary financial programming improves the financial well-being, mental health, and unmet health service needs of urban BEA. Results will contribute timely evidence for utilizing GI as a policy tool to reduce health disparities.Clinical trial registrationhttps://clinicaltrials.gov, identifier NCT05609188.